Daily Income Targets and Passenger Pressure on Safety Risky Riding Behavior Among Online Motorcycle Taxi Riders in Jakarta, Indonesia - Djunaidi, Zulkifli; Khaliwa, Agra Mohamad; Hafia, Azka; Putri, Nadya (Kesmas, 2024)
Online motorcycle taxi riders, a vulnerable group on the road, are more susceptible to serious injury than non-motorcycle riders. This study analyzed a correlation between daily income targets, passenger pressure, risk perception, safety attitudes, and risky riding behavior. This cross-sectional study used a semi-quantitative approach by collecting online-based questionnaires from 500 online motorcycle taxi riders in Jakarta, and 50 of them were obtained through offline interviews. The findings revealed a significant relationship between daily income targets, passenger pressure, risk perception (danger level, stochastic evaluation, and safety priority), safety attitudes (pragmatic attitude to rule violations and dissatisfaction with traffic rules), and risky riding behavior, with a p-value of <0.05. In particular, a pragmatic attitude to rule violations was the most impactful on risky riding behavior. Online motorcycle taxi companies should provide regular training on traffic laws and safe riding practices to improve road safety. This holistic approach may enhance safety through education, passenger awareness, and rigorous management.